A two southern state comparison of the relationship between UCR crime rates and the anticipation of victimization - Dull, R. Thomas (American journal of criminal justice, 1983)
The purpose of this study is to investigate the relationship between UCR crime rates and a surveyed population’s anticipation of victimization within the next year. Separate surveys were conducted within the states of Tennessee and Texas. In both surveys, self-reported questionnaires were mailed to a random sample of 2,000 individuals drawn from the population of persons holding valid driver’s licenses within that state. A comparison was made between six Part I (rape, robbery, assualt, burglary, theft, and vehicle theft) UCR crime rates of the two states and the expectation of imminent victimization, as shown by the statewide surveys. Several past studies have suggested that there is little relationship between the official incidence of crime and the perceived likelihood of victimization. However, this study presents evidence in support of a positive relationship between UCR crime rates and the anticipation of victimization. In addition, it was found that the greater the anticipation of victimization level the more likely the respondents were to utilize defensive security devices (target hardening).